Analyzing the Asymmetric Effect of Macroeconomic Variables on Food Prices in Iran - R. Heydari; E. Javdan; M. Shabanzadeh Khoshrody (مجله اقتصاد و توسعه کشاورزی)
Introduction Food prices are an important indicator of societal well-being, and food inflation can deepen poverty in developing economies. Severe food price fluctuations not only affect food security in developing countries, but also affect economic growth and social stability. Any increase in food prices can push many people back below the poverty line. Rising food prices hit low-income households hard, as the household food basket accounts for nearly half of household living expenses. Therefore, food price stability is of particular importance to policymakers trying to lift households above the poverty line. Food prices in Iran have always been on the rise, and even in recent years, the rate of food price growth has accelerated. Today, inflation, especially food inflation, remains a major problem in Iran, and policymakers are always trying to reduce food inflation. In this regard, and with the aim of controlling food prices, different policies have been implemented in Iran, and the effectiveness of these policies has been discussed. Therefore, understanding the behavior of food prices in response to macroeconomic factors is essential for policymakers to implement appropriate policies at the right time and place to keep domestic prices stable. In this regard, in the present study, the asymmetric effect of macroeconomic variables (money supply, GDP per capita, exchange rate, and trade openness) affecting food inflation in Iran is examined using the nonlinear ARDL approach.